2018
DOI: 10.1080/1369118x.2018.1445273
|View full text |Cite
|
Sign up to set email alerts
|

What drives interaction in political actors’ Facebook posts? Profile and content predictors of user engagement and political actors’ reactions

Abstract: Based on a quantitative content analysis of political actors' Facebook posts (N = 1915), this study investigates profile-level and post-level drivers of user engagement (comments, likes, and shares) by employing a multilevel approach. For the first time in extant research, we also examine the factors that drive political actors to react to user comments. Findings indicate that the number of followers, the use of an official fan profile, and party vote share were negatively related to political actors' reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
127
2
9

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(144 citation statements)
references
References 41 publications
6
127
2
9
Order By: Relevance
“…When there is some kind of interactivity and engagement, it typically takes place with other politicians, especially members of the same party (see Livne et al 2011). However, the finding is not necessarily consistent for all parties: Heiss et al (2018) have argued that politicians from smaller parties were more likely to directly interact with and respond to users. This seems important because the potential influence of the direct mobilisation mechanism as described above might depend at least partly on the extent to which politicians are actually seen as responsive to individual voters, and indeed literature on the subject has suggested that using a more interactive style offers a 'vote dividend' (Koc-Michalska, Lilleker & Smith, 2016).…”
Section: Political Campaigning On Twitter: Mechanisms and Moderators mentioning
confidence: 89%
See 1 more Smart Citation
“…When there is some kind of interactivity and engagement, it typically takes place with other politicians, especially members of the same party (see Livne et al 2011). However, the finding is not necessarily consistent for all parties: Heiss et al (2018) have argued that politicians from smaller parties were more likely to directly interact with and respond to users. This seems important because the potential influence of the direct mobilisation mechanism as described above might depend at least partly on the extent to which politicians are actually seen as responsive to individual voters, and indeed literature on the subject has suggested that using a more interactive style offers a 'vote dividend' (Koc-Michalska, Lilleker & Smith, 2016).…”
Section: Political Campaigning On Twitter: Mechanisms and Moderators mentioning
confidence: 89%
“…is a reply to another user or makes some kind of attempt to engage in a discourse). Empirical research has consistently critiqued politicians for engaging with Twitter in a more broadcast style, and make less use of its interactive features (see Jungherr, 2017, p. 76;Ross & Bürger, 2014), with larger political forces apparently even less likely to interact (Heiss, Schmuck & Matthes, 2018), thus missing out on the potential of the platform. 'Populist' parties are also, apparently, less likely to engage in interaction (Jacobs & Spierings, 2018).…”
Section: Political Campaigning On Twitter: Mechanisms and Moderators mentioning
confidence: 99%
“…Social network sites (SNS) have become an important source for political information as well as political participation (Heiss, Schmuck, & Matthes, 2019). Anytime and anywhere, Facebook users can express their opinions, join discussions, or simply show their support for specific political parties, politicians, and their ideas and make that support visible to their family, friends, and acquaintances.…”
Section: Introductionmentioning
confidence: 99%
“…In social media, politicians need to be more accountable in their actions because citizens using new media have the opportunity to comment and question their doings. Responsibility in online reciprocity with citizens is of great importance as the degree and importance of interaction increases if the political leader answers users (Heiss, Schmuck, & Matthes, 2018).…”
Section: Political Communication and Online Political Engagementmentioning
confidence: 99%